Ensuring the Sustainability of Sadaqah Based Crowdfunding Platforms: The Role of Gamification and User Experience - Nur Aqilah Hazirah Mohd Anim; Suhaida Herni Suffarruddin; Najwa Mohd Najib; Nur Adyani Sabarudin (USIM Press, 2024)
Journal of Muamalatand Islamic Finance Research Vol. 20, No. 1 Page (35-48)